Analisis Hasil Penelitian Pendidikan Agama Islam dengan Pendekatan Ekologi - Ihsan, Muhammad; Abzar, Muhammad (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
Abstract This research aims to identify the results of Islamic Religious Education research and explore and analyze the results of this research using an ecological approach. This research uses library research. Literature studies are obtained from various sources such as scientific journals, books, seminar papers, and related publications. The data analysis paradigm in this research includes data collection, reduction, presentation, and conclusion. The findings in this research are that Islamic religious education is comprehensive and can be integrated with various other scientific disciplines, including the discipline of ecology. The birth of a new concept in an interdisciplinary form between Islamic education and ecology. The object of study of this new concept boils down to ecological conservation, accompanied by Islamic educational values ​​such as repair, maintenance, and preservation of the environment for all living things. The implication is that data sources are limited to online scientific literature. The researcher then uses offline literature to strengthen and enrich ideas of online scientific literature so that the results of the analysis of the results of Islamic education research using an ecological approach can be relied on. The originality/value of the research provides an overview of the Analysis of Islamic Education Research Results with an Ecological Approach which ended in the presence of a new scientific discipline called the ecology of Islamic education. Keywords: Islamic Religious Education, Ecological Approach